Estudo da influência da hidrólise ácida da celulose extraída do capim Mombaça na produção de nanocristais de celulose com diferentes estruturas polimórficas - Martins, Douglas Ferreira (2016)
Given the increasing environmental problems in recent decades, there was a great interest in developing materials that are less harmful to the environment, from renewable and biodegradable sources potentially. Materials based on cellulose nanocrystals (NC) have been widely explored to display thermal properties, mechanical and barrier higher compared to pure polymer or conventional composites, and additionally provide environmental benefits. In this work, NC obtained from the hydrolysis of cellulose Capim Mombaça, with sulfuric acid 11,22M, with different polymorphic structures, were prepared from the addition of water using two procedures: i) isolating the NC(NCMTOT) by diluting the reaction system with water at 5°C and separated by centrifugation and ii) direct centrifugation of NC suspensions to give two fractions: the precipitate (PPT) and supernatant (SOB) were diluted in water at 5°C, and separated again by centrifugation, isolating the NC were called NCMPPT (separated fraction the supernatant as precipitate) and NCMSOB (fraction regenerated or precipitated from the supernatant). The samples NC resulting these processes were characterized by X-ray Diffraction, Atomic Force Microscopy, Viscometry and Thermogravimetric Analysis. The results showed that the procedures adopted for the isolation of NC influenced the size and the physical aspect of the nanocrystals and the type of crystalline cellulose structure (cellulose type I or cellulose type II). It was concluded that changes in the NC thermal stability are associated with the predominant cellulose polymorph, and not merely the presence of sulfate groups on the surface of the nanocrystals as is widespread in literature. In addition, modifications of the hydrolysis process allowed through the thermal decomposition study distinguish the morphology of the nanocrystals from the changes in the activation energy values and make predictions as to the homogeneity of the produced NC.